BANYUMASAN VERB NOMINALIZATION: A TYPOLOGY STUDY - Maria Dimitrij Angie Pavita; Pratama Irwin Talenta (Universitas Respati Yogyakarta (UNRIYO), 2023)
In Cross-Language Typology Studies, there are types of language universality to the languages in it. The focus of this research is that the researcher wants to see what affixes can form verb nominalization in Banyumasan Javanese and also identify the semantic function that results from each of these affixes in Banyumasan Javanese. The results of this study indicate that Banyumasan Javanese (BJB) and Central Javanese (BJS) have nominals in the form of prefixes, suffixes, and confixes. BJB has a variety of types equivalent to BJS. However, in these two languages, both have the nominal confix -an.